A política do Ensino Médio por mediação tecnológica no estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The dissertation discusses the expansion of the supply of Secondary Education in the State of Amazonas through the Presential High School Program through Technological Mediation, implemented by the Amazonas State Department of Education – SEDUC/AM, with the purpose of meeting the demands of this level of education in the regions far from urban centers. We sought to understand the development of this local public policy, within the broad framework of conceptions and strategies that guide public education policies in Brazil, focused on basic education, with a focus on secondary education. The research was developed around the following guiding questions: What are the guidelines for the policy of offering secondary education through technological mediation implemented by SEDUC/AM? To what extent has this policy contributed to the universalization of secondary education in the state of Amazonas? It is a qualitative methodological approach, developed through documentary analysis. The official documents that deal with public policies put into practice through the SEDUC/AM Technological Presence High School Program were analyzed, including the Curricular Pedagogical Proposal and the Curricular Structure of the Program. The results demonstrate that the EMPMT Program was successful in its main guideline, which is to expand the offer of secondary education to rural communities far from urban centers. Despite the quantitative advances in the provision of secondary education to these rural locations, its universalization is far from occurring. There are several contradictions within this public policy, such as the lack of provision of this level of education for students in the morning and afternoon shifts and the lack of curricular content that contemplate the specificities of Amazonian youth, within their realities, which aim to provide bases for the socioeconomic development of these locations. The pedagogical organization of the Program also does not allow the democratic participation of the face-to-face teacher in the pedagogical decisions of the same, having his figure placed as that of a monitor/class assistant. The data reveal that both the municipal, state and federal public authorities are still absent in communities furthest from urban centers, and that actions such as PEMPMT reduce the historical debt that the Brazilian State has with this portion of the population, but it is still a long way off to effect it.
Keywords: Política pública; Ensino médio; Ensino tecnológico; Educação no Amazonas; Tecnologia aplicada à educação; CIÊNCIAS HUMANAS: EDUCAÇÃO; Políticas Públicas; Ensino Médio; Mediação Tecnológica; Programa EMPMT